AB1090 Comparison of Ultrasonographic Joint and Tendon Findings Between Treatment-Naïve Patients with Systemic Lupus Erythematosus and Rheumatoid Arthritis. (9th June 2015) - Ogura, T.; Hirata, A.; Hayashi, N.; Ito, H.; Takenaka, S.; Mizushina, K.; Nakahashi, S.; Fujisawa, Y.; Imamura, M.; Kameda, H.
Abstract : Background: Although both systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) may lead to the joint deformity, lupus arthritis is typically non-erosive and often accompanied by Jaccoud's deformity. Therefore, we examined characteristics of joint and tendon lesions in treatment-naïve patients with SLE and RA by using ultrasonography. Methods: Thirteen treatment-naïve patients with SLE and 39 treatment-naïve RA patients with joint symptoms were included in this study. The hand joints and related tendons were ultrasonographically examined. Their joints and tendons including tendon sheaths were evaluated using a gray-scale (GS) and power Doppler (PD) to a semiquantitative method based on a scale of grades 0 to 3, and the joints or tendons graded as GS ≥2 or PD ≥1 were judged as having joint synovitis and or tendinitis/tenosynovitis. Results: Joint synovitis was observed in 11 of 13 (85%) and 37 of 39 (95%) patients with SLE and RA, respectively, while tendinitis/tenosynovitis were observed in 12 (92%) and 25 (64%) patients with SLE and RA, respectively. SLE patients had tendinitis/tenosynovitis in the wrist joints more frequently (77% versus 36%, p=0.023) as compared with RA. Although the joint synovitis score (GS+PD) per each affected joint was lower in SLE than RA (2.2 versus 2.8, p=0.019), the tendinitis/tenosynovitis showed comparable scores between SLE and RA (1.3 versus 1.0, p=0.446; Figure 1 ). In addition, the concordance of joint synovitis and tendinitis/tenosynovitis in the same region was less in SLE patients (κ=0.21) as compared with RA (κ=0.43). Conclusions: SLE arthropathy is characterized by the relative predominance of tenosynovitis as compared with RA. In addition, tenosynovitis in SLE may develop rather independently from joint synovitis. Disclosure of Interest: None declared